HOW SOUTH AFRICAN SPAZA SHOP OWNERS UTILISE MOBILE COMMUNICATION TECHNOLOGIES TO RUN THEIR BUSINESSES - Matlala, Raymond; Shambare, Richard; Lebambo, Marcia (European Scientific Journal, ESJ, 2014)
The purpose of this study was two-fold. First, it investigated how spaza shop (tuck shop) owners in South Africa utilise mobile communication technologies. Secondly, it evaluated opportunities created by the use of mobile communication devices (e.g. smartphones and tablets) to attain competitive advantage. A survey which sampled 113 micro entrepreneurs operating spaza shops in Hammanskraal (a township in South Africa) was designed. Data were collected through self-completion questionnaires. Findings showed that the use of mobile communication technologies, particularly mobile phones, among micro enterprises was quite high. These were used particularly to communicate with both suppliers and customers. The study also found that in businesses not using ICTs, limited awareness of product functionalities, capabilities and affordability were factors for nonadoption. Given that most South African micro entrepreneurs operate on limited budgets and lack the financial resources to acquire sophisticated ICTs, the greatest value of this research is that it not only confirms the adequacy of mobile technologies in business, but it also shows that consistent usage results in competitive advantage and strategic opportunities.